Effect of Liquamycin® and Syntabac Plus® on gain and health of stockers purchased as steers or bulls - Brazle, F.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Steer calves gained faster (P<.001) and required fewer treatments per animal (P<.01) than newly castrated bull calves during a 29-day receiving period. Liquamycin® (LA-200) injection at arrival increased steer gains (P<.08) and reduced treatments required per animal (P<.08). The combined use of LA-2oo and Syntabac Plus®• increased gains (P<.08) of newly castrated calves.
Keywords: Beef; Liquamycin®; Syntabac Plus®; Stockers